2021
DOI: 10.3171/2021.2.peds20810
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric stereo-electroencephalography: effects of robot assistance and other variables on seizure outcome and complications

Abstract: OBJECTIVE The safety of stereo-electroencephalography (SEEG) has been investigated; however, most studies have not differentiated pediatric and adult populations, which have different anatomy and physiology. The purpose of this study was to assess SEEG safety in the pediatric setting, focusing on surgical complications and the identification of patient and surgical risk factors, if any. The authors also aimed to determine whether robot assistance in SEEG was associated with a change in practice, surgical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The introduction of robotic assistance for intracranial monitoring has brought an enhanced profile for synchronously sampling epileptogenic networks within multiple regions, increasing the accuracy of diagnosis and SOZ delineation. Robotic-assisted placement of intracranial electrodes decreases the operating time, reduces brain entry error and has recently shown to increase surgical outcomes following resective surgery in a selected paediatric population [26]. Intracranial monitoring may even be of value in cases of lesional epilepsy, as a recent report found that up to 56% of MRI lesions partially overlap or may not overlap with the epileptogenic foci found on intracranial EEG [27].…”
Section: Recent Innovations In Surgical Techniquesmentioning
confidence: 99%
“…The introduction of robotic assistance for intracranial monitoring has brought an enhanced profile for synchronously sampling epileptogenic networks within multiple regions, increasing the accuracy of diagnosis and SOZ delineation. Robotic-assisted placement of intracranial electrodes decreases the operating time, reduces brain entry error and has recently shown to increase surgical outcomes following resective surgery in a selected paediatric population [26]. Intracranial monitoring may even be of value in cases of lesional epilepsy, as a recent report found that up to 56% of MRI lesions partially overlap or may not overlap with the epileptogenic foci found on intracranial EEG [27].…”
Section: Recent Innovations In Surgical Techniquesmentioning
confidence: 99%
“…Modern stereotactic neurosurgery commonly uses surgical robots which have further improved accuracy and efficiency when compared with traditional frame-based methods. [37][38][39][40] Fig. 1 Intraoperative photo of an anatomical hemispherectomy for a patient with Rasmussen's syndrome.…”
Section: Stereotaxymentioning
confidence: 99%
“…Modern stereotactic neurosurgery commonly uses surgical robots which have further improved accuracy and efficiency when compared with traditional frame-based methods. 37 38 39 40…”
Section: Minimally Invasive Neurosurgerymentioning
confidence: 99%
“…[5][6][7] The recent advances in neuroimaging, stereotactic targeting, and neurosurgical robotics have led to the increasing use of sEEG throughout North America and the world. [8][9][10][11][12] sEEG is an attractive alternative because it obviates the need to perform a craniotomy prior to localizing the EZ. 13 However, because there are no randomized controlled trials (RCTs) to compare SDE and sEEG invasive monitoring strategies, which of these techniques is 1) associated with fewer complications and 2) associ-ated with the highest success of seizure freedom remains unknown.…”
mentioning
confidence: 99%